Public and Private Schools Students' Anxiety in Online English Language Class During the Covid-19 Pandemic - Maru, Mister Gidion; Angkouw, Larry Gina; Oroh, Elisabeth Z (Celt: A Journal of Culture, English Language Teaching & Literature, 2021)
The implementation of online learning in Indonesian schools as the effect of the covid-19 pandemic raises a relatively new circumstance for students. This research paper reports public and private school students' anxiety in online English language classes. To attain the study objective, the researchers combine qualitative and quantitative methods. Data were collected using questionnaires as the instrument in the quantitative process and interviews in the qualitative method. An 18-item questionnaire based on Likert-scale and closed-ended questions was adapted from Kaisar and Chowdhury. One hundred and thirty-four students of the seven to nine graders of three public and three private junior high schools in Bitung city were the participants in the study. After the survey, the researchers conducted an in-depth interview using a semi-structured pattern. This study revealed that private junior high school students tend to be more anxious than public school students. The students in public schools are more familiar and ready to join online classes than those in private schools. However, both public and private school students do not think that the features of online teaching make them anxious. Students feel dissatisfied and uneasy if the teachers lack creativity and innovation during the online language learning class.